Model Pengembangan Pelayanan Administrasi Terpadu Kecamatan (PATEN) Berbasis Governansi Digital Berkelanjutan - Raniasa Putra; Muhammad Yusuf Abror; Januar Eko Aryansah; Khairunnas Khairunnas; Azhar Azhar; Kiagus Muhammad Sobri; Hoirun Nisyak (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
The article explains District Integrated Administration Service Development Model (PATEN) as part of digital public service and transparancy to the community This is also a competitive model of Rambang Kapak Tengah Regency. The digital feature is reflected on the website development that integrated with surrounding villages. The aim of digital public service is to give simplicity of service to the people. Furthermore, the principle of smart city is transforming outdated method to industry 4.0 approach. Hence the innovation can be started by developing website on Rambang Kapak Tengah Regency. The study makes use of 2 methodology; observation directly to the site to gain potential data and desk study to deepening the analysis of using digital platform on government administrative. The implementation of digital platform as one of smart city’s criteria will provide easier access for people to get information and at the same time deliver accurate information.DOI: https://doi.org/10.26905/abdimas.v6i2.5149